2020
DOI: 10.1021/acs.est.9b04870
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Degradation by •OH during Sediment Oxygenation: Dependence on Fe(II) Species

Abstract: It has been documented that contaminants could be degraded by hydroxyl radicals (•OH) produced upon oxygenation of Fe­(II)-bearing sediments. However, the dependence of contaminant degradation on sediment characteristics, particularly Fe­(II) species, remains elusive. Here we assessed the impact of the abundance of Fe­(II) species in sediments on contaminant degradation by •OH during oxygenation. Three natural sediments with different Fe­(II) contents and species were oxygenated. During 10 h oxygenation of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 53 publications
6
121
0
Order By: Relevance
“…The authors compared the electron transfer rate parameters calculated with a predictive model to experimental parameters available in the literature and concluded that the hydrolysis of hexaquo Fe(II) ions in basic pH favored the inner-sphere mechanism while fully coordinated Fe(II) ion in acid pH favored electron transfer to O 2 using the outer-sphere mechanism. However, Xie et al [63] complemented observations from Rosso and Morgan [65] as well as Hug and Leupin [64] proposing that the electron density of Fe(II) also influenced which mechanism the electron transfer reaction is compelled to proceed at near neutral pH. As for the relative performance of kaolinite and montmorillonite, Xie et al predicted that the ligands ≡Al(III)Oand ≡Fe(III)Oshould attribute greater reactivity to surface-adsorbed Fe(II) in montmorillonite than only ≡Al(III)Oin kaolinite.…”
Section: Reactivity Of Surface Adsorbed Vs Interlayer Vs Structural Fe(ii)mentioning
confidence: 98%
See 3 more Smart Citations
“…The authors compared the electron transfer rate parameters calculated with a predictive model to experimental parameters available in the literature and concluded that the hydrolysis of hexaquo Fe(II) ions in basic pH favored the inner-sphere mechanism while fully coordinated Fe(II) ion in acid pH favored electron transfer to O 2 using the outer-sphere mechanism. However, Xie et al [63] complemented observations from Rosso and Morgan [65] as well as Hug and Leupin [64] proposing that the electron density of Fe(II) also influenced which mechanism the electron transfer reaction is compelled to proceed at near neutral pH. As for the relative performance of kaolinite and montmorillonite, Xie et al predicted that the ligands ≡Al(III)Oand ≡Fe(III)Oshould attribute greater reactivity to surface-adsorbed Fe(II) in montmorillonite than only ≡Al(III)Oin kaolinite.…”
Section: Reactivity Of Surface Adsorbed Vs Interlayer Vs Structural Fe(ii)mentioning
confidence: 98%
“…As for the relative performance of kaolinite and montmorillonite, Xie et al predicted that the ligands ≡Al(III)Oand ≡Fe(III)Oshould attribute greater reactivity to surface-adsorbed Fe(II) in montmorillonite than only ≡Al(III)Oin kaolinite. The authors interpreted their experimental observations for kaolinite and montmorillonite arguing that the interaction of surface-adsorbed Fe(II) with octahedral Fe(III) in montmorillonite stabilized Fe(II) against oxidation being responsible for the slower oxidation rates observed for farmland sediment [63].…”
Section: Reactivity Of Surface Adsorbed Vs Interlayer Vs Structural Fe(ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…Precisely, Xie et al, have argued that ferrous ions released from inosilicates and iron(hydr)oxides naturally present in natural well water samples by mechanical mixing could react with molecular oxygen generating ferric ions and O 2 −• radicals ( Eq. ( 2) ) ( Xie et al, 2020 ). These latter can undergo further disproportion reactions leading to the generation of H 2 O 2 ( Eq.…”
Section: Simultaneously Monitoring Of Viability (Dvc-fish) and Culturability (Plate Count-pc) During Bacteria Inactivation In Groundwatermentioning
confidence: 99%